PERANCANGAN SISTEM INFORMASI COMPANY PROFILE DAN PEMESANAN LAYANAN JASA BERBASIS WEB PT GEOTERRA - Muhammad Zidane Damara; Edo Arribe (LPPM Universitas Putera Batam, 2023)
The company profile information system is a method used by companies to introduce themselves to the general public and convey information about the type of business they are engaged in. This Website is very beneficial for PT.Geoterra and its clients, as clients do not need to visit the company to order their services. The system can minimize costs for clients, leading to the development of an easily accessible information system that provides Details regarding the corporation and what it provides.. positive impact on company is that it gains a broader reach since the system can be accessed by clients through computers and mobile devices. The company profile information system is designed using the Waterfall method, with data collected through literature studies, interviews, and observations. The result is an efficient and effective system that provides comprehensive and engaging information to users and potential clients.